Is urban farming in the global south potentially a temporary phenomenon? - Drechsel, Pay (2022)
Spatio-temporal analyses from several cities in sub-Saharan Africa showed a mixed picture with inner-urban farmers shifting to the urban fringe, and increases in urban agriculture, as well as declining urban farm lands in other cities. The key drivers influencing the direction of change are population pressure, official support (or lack thereof) of urban farming, land tenure and geographical factors such as land suitability and water access.